Logotherapy and Existential Analysis - McLafferty, Jr., Charles L.; Levinson, Jay (Logotherapy and Existential Analysis: Proceedings of the Viktor Frankl Institute Vienna, 2024)
XXIII, 418 p. 17 illus., 12 illus. in color.